Effect of strain rate and temperature on press forming of extruded WPC profiles. (15th November 2017) - Toghyani, Amir E.; Amraei, Mohsen; Matthews, Sami; Varis, Juha; Kärki, Timo; Zhao, Xiao-Ling
Abstract: Wood-plastic composites (WPCs) are experiencing rapid market growth in manufacturing industries. In view of the attractive qualities of this material and on-going development of new production processes and post-production processes, great potential for widespread utilization of WPCs clearly exists. This paper evaluates the temperature effects on forming of an extruded WPC material in a post-production process. The press-forming process described in this work is used to form a pre-determined profile shape for the final product. After preliminary tests to find suitable temperature ranges, a diverse set of material behavior tests were conducted on pre-heated sheets of the WPC material. Numerical simulation was also performed using LS-DYNA software to evaluate formability of the WPC. Simulated and experimental values were in good agreement, indicating the feasibility of using the simulation approach for preliminary evaluation of formability of WPCs.